Kiai Leadership Patterns in The Modernization of Boarding School Management - Nur Khamid (Universitas Nurul Jadid, 2024)
This study explores the leadership patterns of kiai in the effort to modernize pesantren management, with the aim of understanding how kiai leadership can combine traditional values with the demands of modern management. The main focus of this study is to identify the dual role of kiai as spiritual and managerial leaders, and their impact on the operational effectiveness of pesantren. Using a qualitative method with a case study approach, data were collected through in-depth interviews and observations in several pesantren that have implemented modern management principles. The results of the study indicate that kiai leadership that successfully combines traditional and modern aspects results in more efficient pesantren management without sacrificing the religious values that are the foundation of the institution. In addition, this leadership pattern also strengthens the identity of the pesantren amidst the flow of globalization, maintaining the relevance of the institution while maintaining its uniqueness. These findings indicate that modernizing pesantren management through kiai leadership not only increases operational efficiency but also strengthens the competitiveness and resilience of pesantren in the long term. This study makes an important contribution to understanding how pesantren can adapt to the times without losing their traditional essence, as well as opening up opportunities for further research on the application of modern management in religious-based educational institutions.